Effects of a 10-week athletic performance program on match performance variables in male professional football players - Jiménez Rubio, Sergio; Estévez Rodríguez, José L.; Escamilla Galindo, Victor; Jiménez-Sáiz, Sergio L.; Del Coso, Juan (Frontiers in Sports and Active Living, 2025)
IntroductionThe aim of this study was to evaluate the effect of an Athletic Performance Program (APP), implemented as a complement to the usual training routines of a professional football team, on match performance variables in professional football players. The APP was designed to target mobility, stability, strength, multidirectional and sprint skills, which are critical for performance during competitive matches.MethodsA prospective quasi-experimental study was conducted over three consecutive seasons. Fifty-four professional football players were randomly allocated into a control group (CG, n = 25) and an experimental group (EG, n = 29). During the in-season period, both groups followed the standard training routines prescribed by the coaching staff. Additionally, the CG performed a general supplementary physical fitness program five times per week, while the EG undertook the APP with the same frequency. The APP included indoor track sessions and micro-doses of on-field stimuli, focusing on specific performance attributes. The interventions lasted 10 weeks. Performance metrics were assessed pre- and post-intervention using GPS to measure match-related variables (total running distance, sprint distance, number of sprints, and peak running speed) and countermovement jump tests to evaluate vertical jumping ability. A two-way ANOVA (2 × 2; group and time) was employed to analyze the effects of the interventions and their interaction.ResultsSignificant group × time interaction effects were observed for total running distance (F = 51.853, P < 0.001), sprint distance (F = 197.610, P < 0.001), number of sprints (F = 86.923, P < 0.001), and peak running speed (F = 81.351, P < 0.001) during matches. Post-hoc pairwise comparisons revealed that only the EG showed improvements across all performance variables: total running distance (117.5 ± 5.20 to 123.1 ± 3.5 m/min, P < 0.001), sprint distance (6.45 ± 1.43 to 8.35 ± 1.22 m/min, P < 0.001), number of sprints (0.14 ± 0.03 to 0.16 ± 0.03 sprint/min, P < 0.001), and peak running speed (31.1 ± 1.3 to 32.1 ± 1.0 km/h, P < 0.001). Conversely, the CG exhibited significant declines in these metrics post-intervention (P < 0.001).DiscussionThe findings demonstrate that integrating a 10-week multicomponent Athletic Performance Program into traditional training routines is effective in enhancing match performance variables, particularly in high-intensity actions such as sprints and running speed. The APP's focus on mobility, stability, strength, and sprint-specific skills likely contributed to these improvements, highlighting the importance of targeted supplementary training for optimizing athletic performance in professional football players. The observed decline in the CG emphasizes the need for specialized interventions to maintain and improve performance during the season.